2014
DOI: 10.1155/2014/150968
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Wear Analysis of Zinc Phosphate Coated Engine Oil Ring and Cylinder Liner Tested with Commercial Lubricant

Abstract: The objective of this study was to evaluate the tribological performance through investigating protective additive layer and friction coefficient and implementing the quantitative wear measurements on the rubbed surface of the sliding pairs. The specimens of oil ring were rubbed against cast iron engine cylinder liner under boundary lubrication conditions. The ring and liner surfaces were examined by optical, scanning electron microscope and atomic force microscopy. The elemental analysis of surfaces was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Volume 68 • Number 4 • 2016 • 482-496 These sides did not rub with the cylinder liner surface directly but they rubbed with the piston ring groove. Zinc phosphate coating has low coating thickness and hardness and can remove from the surface in the reciprocating motion, as Doguş et al (2014) indicated in their study. It is known that boron is a light element and it is hard to detect boron with EDX analysis; for this reason, boron was not detected on the NP-3 oil-lubricated surfaces.…”
Section: Industrial Lubrication and Tribologymentioning
confidence: 73%
“…Volume 68 • Number 4 • 2016 • 482-496 These sides did not rub with the cylinder liner surface directly but they rubbed with the piston ring groove. Zinc phosphate coating has low coating thickness and hardness and can remove from the surface in the reciprocating motion, as Doguş et al (2014) indicated in their study. It is known that boron is a light element and it is hard to detect boron with EDX analysis; for this reason, boron was not detected on the NP-3 oil-lubricated surfaces.…”
Section: Industrial Lubrication and Tribologymentioning
confidence: 73%
“…In addition, only wear transfer elements (Cr, Si and Mn) were detected on the oil ring surface, lubricated with NPNA, as can be seen in X-ray spectra of Figure 7(d). The detected calcium content on the oil ring surface was from the zinc phosphate coating of piston ring due to modification with calcium to get higher wear corrosion resistance (Özkan and Kaleli, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Iron phosphate, zinc phosphate and manganese phosphate are three common phosphate coatings. In order to obtain the wear trend of zinc phosphate coating, Özkan and Kaleli 57 conducted tests between zinc phosphate piston ring (Honda GH-200 engine) and gray cast iron cylinder liner (Honda GX-390 engine) on a reciprocating tribotester under boundary lubricating conditions. It was found that the proportion of calcium, zinc and phosphorus in the piston ring decreased and transferred to the cylinder liner surface.…”
Section: Other Coating Technologymentioning
confidence: 99%